2017
DOI: 10.1016/j.polymer.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mesostructured ZnO/Au nanoparticle composites with enhanced photocatalytic activity

Abstract: Ease of catalyst separation from reaction mixtures represents a significant advantage in heterogeneous photocatalytic wastewater treatment. However, the activity of the catalyst strongly depends on its surface-to-volume ratio. Here, we present an approach based on cylindrical polybutadiene-block-poly(2-vinylpyridine) polymer brushes as template, which can be simultaneously loaded with zinc oxide (ZnO) and gold (Au) nanoparticles. Pyrolytic template removal of the polymer yields in mesostructured ZnO/Au composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Those micelles are able to enhance synergistic effects on catalysis. [ 206 ] Also, they manufactured patchy nonwovens using amidated‐SEM wCCMs and PS via coaxial electrospinning and then embedded Au NPs onto them. [ 188 ] The hybrid patchy nonwovens can be used as an efficient and reusable catalysis platform.…”
Section: Applications Of Nano‐objects In Cdsa or Pi‐cdsa Systemmentioning
confidence: 99%
“…Those micelles are able to enhance synergistic effects on catalysis. [ 206 ] Also, they manufactured patchy nonwovens using amidated‐SEM wCCMs and PS via coaxial electrospinning and then embedded Au NPs onto them. [ 188 ] The hybrid patchy nonwovens can be used as an efficient and reusable catalysis platform.…”
Section: Applications Of Nano‐objects In Cdsa or Pi‐cdsa Systemmentioning
confidence: 99%
“…Consequently, considerable efforts were done to overcome this inconvenience along with characteristic high probability for the recombination of photogenerated charge carriers. Innovative approaches demonstrated that by coupling the ZnO with various narrow band-gap materials (metallic and nonmetallic ions [82][83][84] noble metals and oxides [85][86][87][88] or polymer-based materials [89,90] etc. ), it was possible to modulate the band-gap energy and shift the absorption wavelength to the visible region.…”
Section: Zno Nanoparticlesmentioning
confidence: 99%
“…It may be additionally enhanced by the localized surface plasmon resonance effect of the Au nanoparticles. 76 The non-woven mesostructure, moreover, ensures easy recovery from the liquid reaction medium.…”
Section: Example II Colloidal Routementioning
confidence: 99%